Human leukocyte antigen (HLA)-DRB1 allele polymorphisms and systemic sclerosis. Issue 6 (2nd November 2019) - Xu, Yanzhen; Mo, Nanfang; Jiang, Zhiwen; Lu, Shaoming; Fu, Shien; Wei, Xinyan; Zhao, Dong; Xie, Zhibin; Jia, Wenxian; Liu, Jiayi; Wang, Xiao; Shi, Dongchen; et al.
Abstract: Objectives: Human leukocyteantigen (HLA) is the most important gene for immune system regulation. Although studies have evaluated the association between HLA-DRB1 allele polymorphisms and systemic sclerosis (SSc), their results are still controversial. We performed a meta-analysis to assess the association of HLA-DRB1 alleles with risk of SSc. Methods: Electronic database were systematically searched for articles, a total of 11 case–control studies including 3268 cases and 5548 controls were analyzed. Odds ratio (ORs) and 95% confidence intervals were used to assess the association of HLA-DRB1 alleles with SSc. The relationship between SSc-related autoantibodies and DRB1 alleles was also analyzed. Results: In the overall analysis, four alleles (DRB1*04:03, DRB1*08, DRB1*11, and DRB1*11:04) increased the risk of SSc; however, five alleles (DRB1*07, DRB1*11:01, DRB1*13, DRB1*13:01, and DRB1*14) had the opposite effect. Analysis of subgroups by ethnicity indicate that DRB1*11:01 and DRB1*13:01 confer a protective effect in Caucasians, while DRB1*11:04 was associated with a higher risk of SSc. For Asian, DRB1*13:02 was found to be a protective factor. In addition, the frequency of DRB1*11:04 alleles was significantly increased in ATA + SSc patients compared with ATA − SSc patients. Conclusion: DRB1*04:03, DRB1*08, DRB1*11, and DRB1*11:04 were associated with the risk of SSc. Additionally, DRB1*11 and DRB1*11:04 were association with ATAs.